2019
DOI: 10.48550/arxiv.1901.07139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hamilton Cycles in Random Graphs: a bibliography

Abstract: We provide an annotated bibliography for the study of Hamilton cycles in random graphs and hypergraphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 144 publications
(187 reference statements)
3
17
0
Order By: Relevance
“…This generalizes Johansson's result, as well as the result by Bollobás and Frieze, and answers a question by Frieze (see [8], Problem 20).…”
Section: The Random Subgraph Processsupporting
confidence: 89%
“…This generalizes Johansson's result, as well as the result by Bollobás and Frieze, and answers a question by Frieze (see [8], Problem 20).…”
Section: The Random Subgraph Processsupporting
confidence: 89%
“…Proof of Theorem 2.4. Let d = log n/300 and let i 0 , i 1 , i 2 and i 3 be as in (9). Let D 0 , D (v) = 0, and thus, for each 0 ≤ i ≤ i 1 the property in Theorem 2.4 for D i holds trivially.…”
Section: Proof Of Theorem 24 From Theorem 23mentioning
confidence: 99%
“…Independently, Bollobás [4], and Ajtai, Komlós and Szemerédi [1], showed that, in almost every random graph process, the first graph G i with minimum degree at least 2 is Hamiltonian. Further results on the Hamiltonicity of random graphs, including counting and packing results, can be found in Frieze's comprehensive bibliography [9].…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate this, we take a closer look at the Erdős-Rényi random graph G n,p which is an n-vertex graph with each edge being present independently with probability p. The existence question of the Hamilton cycle problem is very well understood, cf. the comprehensive survey by Frieze [13]. Let H be the set of Hamiltonian graphs, then for G n,p it holds that (Komlós and Szemerédi [19] and Korshunov [20])…”
Section: Introductionmentioning
confidence: 99%